(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Pyrus korshinskyi (Pyrus korshinskyi Litv.) is a rare endemic species of the walnut-fruit forests of the Western Tien Shan and Pamir-Alai, currently listed as endangered and included in national and regional Red Data Books. In Kyrgyzstan, this species occurs in the Chatkal and Fergana ranges, where it grows either in groups or as solitary trees at altitudes of 1200–2000 m above sea level. This study investigates the morphological and biological characteristics of its fruits and seeds. The results revealed that the average fruit mass is 47.30 ± 0.46 g, with a mean height of 4.04 ± 0.38 cm and a diameter of 4.58 ± 0.32 cm. The five-loculed ovary contains a variable number of seeds, which include both fully developed and aborted ones. The average yield of viable seeds amounted to 0.981 ± 0.11% of the total fruit mass. The results indicate a low level of seed productivity in P. korshinskyi, underscoring the need for further studies and the development of effective in situ and ex situ conservation measures.